Two species of philometrid nematodes (philometridae) from marine fishes off Japan, including Philometroides branchiostegi sp. n. from Branchiostegus japonicus (malacanthidae) - Moravec, Frantisek; Nagasawa, Kazuya; Nohara, Kenji (Folia parasitologica, 2012)
Gravid females of two species of philometrid nematodes (Philometridae) were collected from marine perciform fishes in Japanese waters, mainly from the southern Sea of Japan. Based on light microscopy and scanning electron microscopy examinations, the previously described but poorly known species Philometra cryptocentri Yamaguti, 1961 is redescribed from specimens recovered from the abdominal cavity of Acanthogobius flavimanus (Temminck et Schlegel), Pterogobius elapoides (Günther) and P. zonoleucus Jordan et Snyder (all Gobiidae) (all new host records); the number (14) and arrangement of cephalic papillae in this species are described for the first time. The new species, Philometroides branchiostegi sp. n. from head tissues of Branchiostegus japonicus (Houttuyn) (Malacanthidae), based on a single specimen, is mainly characterized by the embossment of the entire body except for the cephalic end, presence of four submedian pairs of large cephalic papillae of external circle and two small lateral single papillae of internal circle, pair of large papilla-like caudal projections, the oesophagus with a distinct anterior inflation, by a markedly small body (length about 18 mm) and the larvae 306-465 microm long.
Keywords: Female; nemoci ryb; infekce hlísticemi řádu Spirurida; Animals; ženské pohlaví; mužské pohlaví; Male; Spirurida; zvířata; Spirurida Infections; Perciformes; Fish Diseases